Surface Water Quality Status in the part of Bhadravathi Industrial Town, Shimoga District, Karnataka, India. (Global Journal of Science Frontier Research, 2011)
In order to know the surface water pollution in the part of Bhadravathi industrial town, Shimoga District, Karnataka state, the present study has been conducted around Mysore Paper Mill (MPM) solid waste dump site, which may be the source of pollution. Nine surface water samples were collected and analyzed for physico-chemical parameters and heavy metal concentrations. The results indicated that the concentration of Na is high in two samples and very high in three samples. The increase in the concentrations of Na and K in surface water samples may be probably due to the agricultural run-off and effluents discharged from the industries.
Keywords: Physico-chemical; Bhadravathi; Mysore Paper Mill